2016
DOI: 10.1021/acsnano.6b03655
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectronic Investigation Reveals the Electrochemical Basis of Electrical Conductivity in Shewanella and Geobacter

Abstract: The electrical conductivity measured in Shewanella and Geobacter spp. is an intriguing physical property that is the fundamental basis for possible extracellular electron transport (EET) pathways. There is considerable debate regarding the origins of the electrical conductivity reported in these microbial cellular structures, which is essential for deciphering the EET mechanism. Here, we report systematic on-chip nanoelectronic investigations of both Shewanella and Geobacter spp. under physiological conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 42 publications
1
32
0
1
Order By: Relevance
“…Understanding, and subsequently maximizing the interfacial charge transfer rate in semi-artificial photoanodes, will be key towards boosting photocurrent densities towards practical levels. Here, a host of techniques that have been established on simpler platforms (confocal fluorescence microscopy 54 , electrochemical impedance spectroscopy 55 , surface-enhanced Raman/infrared spectroscopy 56,57 , and nano-electrodes 58,59 ) can provide a wealth of mechanistic information for this set of systems. For example, spectroscopically detecting the secretion of diffusional mediators or redox changes in membranebound cytochromes can implicate their role in the microorganisms' charge transfer mechanism to an electrode.…”
Section: Semi-artificial Water Oxidationmentioning
confidence: 99%
“…Understanding, and subsequently maximizing the interfacial charge transfer rate in semi-artificial photoanodes, will be key towards boosting photocurrent densities towards practical levels. Here, a host of techniques that have been established on simpler platforms (confocal fluorescence microscopy 54 , electrochemical impedance spectroscopy 55 , surface-enhanced Raman/infrared spectroscopy 56,57 , and nano-electrodes 58,59 ) can provide a wealth of mechanistic information for this set of systems. For example, spectroscopically detecting the secretion of diffusional mediators or redox changes in membranebound cytochromes can implicate their role in the microorganisms' charge transfer mechanism to an electrode.…”
Section: Semi-artificial Water Oxidationmentioning
confidence: 99%
“…417 A very recent report argues, based on experimental evidence, that the mechanisms for all longrange transport reports are electrochemical nature. 418 Flickering resonance (FR), mentioned in sections 2.2 and 2.2, and in the discussions of 5 and 7). 110 The FR model accounts for both exponential distance dependence and partial excess charge location on the bridge.…”
Section: Electronic and Structural Properties Of Immobilized Proteinsmentioning
confidence: 99%
“…Moreover, another study reported that the mechanism of charge transport in live biofilms of G. sulfurreducens was entirely mediated by redox reactions between the cells and the electrode, with charge neutrality provided by the movement of ions in solution. [98] The complex chemical composition and, therefore, electronic properties of biofilms make the comparison of experiments on biofilm to those on purified proteins-as some researchers have done-potentially misleading. [31,34,99] Moreover, individual protein nanowires are already challenging for electronic characterization.…”
Section: Impact Of Ions On Protein Materials Electronic Propertiesmentioning
confidence: 99%
“…[123] Even electrode area has been reported to change current-voltage responses in G. sulfurreducens biofilms. [98] For all these reasons, electrode design requires careful consideration; differing geometries may lead to different observed conduction mechanisms and complicate comparison between various conductive protein materials.…”
Section: The Importance Of Measurement Setupmentioning
confidence: 99%